Major General Lev Yegorovich Nord as Governor of Ufa (1889-1894) - R. I. Kantimirova (Научный диалог, 2020)
The activity of the Ufa governor Lev Yegorovich Nord is considered. The scientific novelty of the study is that the activities of the governor are covered on the basis of an analysis of unpublished sources. The author shows that the efforts of the Ufa governor L. Ye. Nord and local authorities implemented a set of measures, most of which had a positive effect on the socio-economic development of the region. It is shown that much attention was paid to the land issue, the preservation of the natural wealth of the Southern Urals, the rights of Bashkir patriarchs to freely alienate their lands. The successful work of L. Ye. Nord in lean years of 1890-1891 is emphasized. The article describes social activities: providing an opportunity for the starving population to earn money for food, introducing quarantine in the province in connection with the cholera epidemic, in particular the isolation of patients in specially designated barracks. It is reported that with the assistance of the governor, a highway was laid, the construction of an elevator in Ufa and a grain barn in Davlekanovo was started. The author comes to the conclusion that the activity of the Ufa governor was aimed exclusively at the good of the Fatherland, brought great benefits to the region, which caused respect for his contemporaries.